Begunci in Slovenci - Dragoš, Srečo (Socialno delo, 2016)
In the early 1990s, during the disintegration of our ex common state of Yugoslavia, when the new state of Slovenia was established, we received approximately 70,000 refugees (amounting to 3.5% of the population of Slovenia). Despite this massive intake of refugees, at that time Slovenia didn't disintegrate and no social stratum's living standard deteriorated, although at that time Slovenia was regarded as a rather uncertain project, was faced with a serious economic crisis and unemployment, and the outcome of war on the Balkans looked completely unpredictable. The situation today is the opposite: there are practically no refugees in Slovenia, and our country is the second most restrictive country in Europe (both in absolute and relative numbers), as far as getting protected against them is considered. The backdrop of this anti-refugee panic is related to a very negative structure and trends of public opinion in the key fields of societal and systemic integration. Regarding a pronounced tendency toward increased poverty and decomposition of basic mechanisms of the welfare state, the public opinion of the Slovenes is progressively moving in an authoritarian direction, is getting susceptible to patriotic sentiments and uncritical glorification of "Sloveneness", but at the same time it is rejecting capitalism and (again) getting enthusiastic about socialism. Therefore all conditions are met for an evolution of events similar to those from the first half of the 20th century - in other words, for national socialism.
Keywords: nacionalsocializem; socializem; socialism; avtoritarni sindrom; authority syndrome; panika; panic; demokracija; democracy; national socialism